PERAN INFLUENCER INSTAGRAM DALAM MEMBENTUK OPINI PUBLIK DAN PARTISIPASI POLITIK - Juliana Saragih; Mona Purba; Monica Manik; Nadila Dwi Aulia; Wiga Wulandari; Oksari Anastasya Sihaloha (Journal Education and Government Wiyata, 2024)
This research aims to explore how Instagram influencers shape public opinion and contribute to political participation among specific demographic groups in the digital era. This study employs qualitative methods, specifically content analysis of Instagram influencer activities during political campaigns, as well as in-depth interviews with social media users who actively follow influencers and physics students at Medan State University. In a political context, influencers are often used by political actors to introduce candidates, disseminate campaign-related information, and mobilize support. Moreover, influencers also contribute to encouraging political participation among the community, particularly among the younger generation, through a more relaxed and accessible approach. Therefore, this study suggests stricter regulations regarding the role of influencers in the political realm as well as better digital literacy for society to avoid the negative impact of information spread on social media.